PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MODEL DIRECT INSTRUCTION - Sukrorini, Wiwik (Jurnal Pendidikan Matematika dan IPA, 2014)
This study was motivated by the study of matter form roots and rank Numbers are still low.Therefore, the teacher will use the Direct Instruction model of which aim to improve student learning outcomes grade IX SMP 23 Pontianak. The subjects were students of grade IX A second semester of 2013/2014. The study lasted for 2 cycles, where in the first cycle showed an average of 71,60 while the learning outcomes in the second cycle, the average results of study show the score 72.14. The mastery learning of students in the first cycle is only 39% of all student in the class, whereas in the second cycle, mastery learning  reaches 57%.Teacher performance assessment by the observer in the first cycle on average 70.95 and the second cycle averaged 72.28. Thus, learning the Direct Instruction model can improve learning outcomes as well as the percentage of mastery learning . Based on the research results, the learning Mathematics Direct Instruction model can be used as an alternative learning strategies that can be implemented in an effort to improve learning outcame. Keywords: Direct Instruction Model.